RESPON PERTUMBUHAN DAN PRODUKSI BEBERAPA VARIETAS KACANG TANAH (Arachis hypogaea L.) PADA PERBEDAAN PEMBUMBUNAN - Dali, Dali; Gusmiatun, Gusmiatun; Supeno, Gandi (Universitas Muhammadiyah Palembang, 2020)
Growth Response And Production Several Varieties of Peanut (Arachis hypogaea L.) On pile difference.This research was conducted attheexperimental Agro Technology Faculty of Agriculture, University of Palembang and University of Muhammadiyah Palembang in farmer's garden, Sukajaya Village, Sukarame District, Palembang City., this study was conducted in May 2019 to August 2019. The method used is a split plot design (Split-plot design) with 9 treatment combinations and repeated 3 times. The treatment given is: Main Plot: Pile (P) consisting of: P0 = Without Pile, P1 = Pile1 times, P2 = Pile 2 times. and Son Plot: Varieties (V) consisting of: V1 = Variety Rabbit, V2 = Variety Giraffes, Elephants V3 = Variety. The parameters measured were (1). Plant height (cm), (2). Number of Branch Primary (stalk), (3). Number of pods / plant, (4). Weight pods / plant (g), (5). Weight pods / plot (kg), (6). Empty Pods percentage (%), (7). Berangkasan Dry Weight (g). The results showed that treatment of type varieties are very significant effect on all the observed variables. Pile effect no significant effect on variable number of branches, weight of 100 seeds, weight berangkasan dry and significant and very real on plant height, number of pods cropping, number of pods perpetak, while their interaction very significant effect on the observed variables pods crop and the number of perpetak pods and no real effect on plant height, number of branches, the percentage of empty pods, weight of 100 seeds, and dried berangkasan weight. Giraffes varieties give the best effect on the growth and production of groundnut (Arachis hypogea L.), treatment pile twice give the best effect on the growth and production of groundnut (Arachis hypogea L.) and Treatment varieties Giraffe and pile twice give the best effect against growth and production of groundnut (Arachis hypogea L.) with production of 1.68 tons / ha.